Smoke and mirrors short fictions and illusions - Gaiman, Neil (Avon Books, 1998)
A collection of fantasy stories and poems. In Chivalry, a woman discovers the Holy Grail in a secondhand shop, in Murder Mysteries, an angel visiting Los Angeles provides the inside story on Lucifer's revolt against God, and there are revisionist stories on Snow White and Santa Claus.